2016
DOI: 10.1111/jrh.12170
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Mass Index and the Trajectory of Depressive Symptoms Among Rural Men and Women

Abstract: Our findings hold important public health implications given the increasing rates of overweight and obesity over the past couple of decades, particularly among rural adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…The results of this study demonstrated that the respondents with lower BMI reported higher depression scores. Although many studies suggested that overweight or obesity is a risk factor for depression [51][52][53], our study results was consistent with one study based on population of China [54]. We found that the studies based on European and American sample population all reported the positive relationship between BMI and depression, but a few studies were reported in China.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study demonstrated that the respondents with lower BMI reported higher depression scores. Although many studies suggested that overweight or obesity is a risk factor for depression [51][52][53], our study results was consistent with one study based on population of China [54]. We found that the studies based on European and American sample population all reported the positive relationship between BMI and depression, but a few studies were reported in China.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical obesity, one of the major causes of preventable disease and one of the largest epidemics facing patients today, has more than doubled in the last three decades Chang et al [2], Preiss et al [3]. This information is disconcerting and it is vital that healthcare professionals demonstrate healthy behaviors while counseling clinically obese and overweight depressed patients to become physically active though behavioral health, lifestyle medicine, and population health interventions.…”
Section: Review Of Literature Conclusionmentioning
confidence: 99%
“…It is well documented that multiple obesity-depression co-variations occur across populations [2,[6][7][8]. A 2017 study by Pereira-Miranda, Costa, Queiroz, Pereira-Santos, and Santana, published in the Journal of the American College of Nutrition reports that patients with obesity were 32% more likely to have depression compared to those who were eutrophic (patients within the normal BMI range).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations